2021
DOI: 10.2169/internalmedicine.6063-20
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag in Combination with Rabbit Anti-thymocyte Globulin/Cyclosporine A in Immunosuppressive Therapy-naïve Patients with Aplastic Anemia in Japan

Abstract: Objective In Japan, immunosuppressive therapy (IST) with anti-thymocyte globulin (ATG), and cyclosporine A (CsA) is the standard of care in patients with aplastic anemia (AA) who are not indicated for stem-cell transplantation, although some patients may experience relapse. This study assessed the efficacy and safety of eltrombopag in combination with rabbit-ATG/CsA in IST-naïve patients with non-severe or severe AA in Japan. Methods In this non-randomized, open-label, single-arm, phase II study, rabbit-ATG/Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(47 reference statements)
0
8
0
1
Order By: Relevance
“…In Japan, the most common adverse event was myalgia, followed by hyperbilirubinemia, which is resolved with EPAG dose reduction or brief interruption of the regimen. (Imada et al, 2021;Jie et al, 2021;Tremblay et al, 2019) The adverse effects of EPAG bring additional cost to the system, as they are absent in the GAT + Cyclosporine group, but when compared to the adverse effects of this second group, the EPAG does not add a statistically significant cost. (Tremblay et al, 2019) The costs for the IST with the addition of the EPAG are still an important obstacle to its acquisition by health services financed by the Unified Health System of Brazil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, the most common adverse event was myalgia, followed by hyperbilirubinemia, which is resolved with EPAG dose reduction or brief interruption of the regimen. (Imada et al, 2021;Jie et al, 2021;Tremblay et al, 2019) The adverse effects of EPAG bring additional cost to the system, as they are absent in the GAT + Cyclosporine group, but when compared to the adverse effects of this second group, the EPAG does not add a statistically significant cost. (Tremblay et al, 2019) The costs for the IST with the addition of the EPAG are still an important obstacle to its acquisition by health services financed by the Unified Health System of Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Non-medical and indirect costs and the fees of the professionals involved, were not evaluated. (Imada et al, 2021;Jie et al, 2021;Saúde, 2010) A theoretical simulation of a typical patient was used as a basis for cost calculation, which would be followed up by a pediatric hematology service in the state of Sergipe, which is as part of Brazil's Unified Health System. Based on the literature, the typical patient is male, 14 years old, weighing 49 kg, without previous immunosuppressive therapy use, with a history of more than 20 blood transfusions, without family history of hematological disease.…”
Section: Methodsmentioning
confidence: 99%
“… 25 However, in a recent study of ELTR in combination with rabbit ATG/CsA in treatment-naïve patients with AA by Imada and colleagues, clinically significant clonal evolution or cytogenetic abnormalities were also not observed during a long follow-up. 29 De Latour and colleagues showed that the prevalence of somatic mutations was not higher in the ELTR group than in the IST group. 26 Therefore, the role of adding ELTR upfront in boosting clonal evolution is still unclear, and a much longer follow-up is needed to shed light on this issue.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, erythrocyte response rate was much lower than that of granulocyte and megakaryocyte. Thus, for NSAA patients suffering from anemia, more aggressive treatment such as CsA combined with ATG, androgen or eltrombopag should be considered ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%